Helmintos de la República de Costa Rica XVII. Una nueva especie de Euryhelmis (Trematoda: Heterophyidae), parásito de Mustela frenata costaricensis - Brenes, Rodrigo Ramòn (1960)
The genus Enrybelmis Poche, 1926 is revised and a new diagnosis propossed to amend the discrepancies found in the literature. A new species, E. costaricensis, found in the intestine of a weassel (Mustela frenata costaricensis) is described, widenning the geographic distribution for the genus.